2020
DOI: 10.1111/jcmm.15298
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation‐mediated down‐regulation of lncRNA TBX5‐AS1:2 in Tetralogy of Fallot inhibits cell proliferation by reducing TBX5 expression

Abstract: Tetralogy of Fallot (TOF) is the most common complex congenital heart disease (CHD) with uncertain cause. Although long non‐coding RNAs (lncRNAs) have been implicated in heart development and several CHDs, their role in TOF is not well understood. This study aimed to investigate how dysregulated lncRNAs contribute to TOF. Using Gene Expression Omnibus data mining, bioinformatics analysis and clinical heart tissue sample detecting, we identified a novel antisense lncRNA TBX5‐AS1:2 with unknown function that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…We found for the first time in CRC that they co-expressed with DEAGs and may be involved in the process of autophagy in CRC. TBX5.AS1 is significantly down-regulated in damaged heart tissue of tetralogy of Fallot ( 40 ). TBX5.AS1 has been found to be a prognostic factor for lung adenocarcinoma ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found for the first time in CRC that they co-expressed with DEAGs and may be involved in the process of autophagy in CRC. TBX5.AS1 is significantly down-regulated in damaged heart tissue of tetralogy of Fallot ( 40 ). TBX5.AS1 has been found to be a prognostic factor for lung adenocarcinoma ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…TBX5-AS1:2 lncRNA regulates Tbx5 expression via modulation of its promoter methylation status. Curiously, TBX5-AS1:2 lncRNA is dysregulated in Tetralogy of Fallot patients, suggesting a plausible role in the onset of this cardiac congenital defect [ 160 ]. Additionally, Tbx5ua , a lncRNA close to Tbx5 locus is required for proper ventricular wall development, and thus being necessary for embryonic development, since Tbx5ua mouse knock-out embryonic lethal [ 161 ] ( Figure 1 A,D) .…”
Section: Post-transcriptional Control Of Heart Fields Deployment By N...mentioning
confidence: 99%
“…On the other hand, it has been demonstrated that the TBX5 gene is modified by different epigenetic mechanisms, including long non-coding RNAs (lncRNAs), histone modification and polycomb group proteins. These epigenetic modifications play a key role in the pathophysiology of CHDs [ 14 , 15 , 16 , 17 ]. Furthermore, some studies have shown that an imbalance in the status of DNA methylation could change the expression of genes that participate in cardiogenesis [ 8 , 10 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%